ZAKAT and Poverty Alleviation - Mohd Mahyudi Mohd Yusop (IIUM PRESS, 2015)
This edited book aim to raise issues pertaining to the topic of zakat anad its primary goal of poverty alleviation. it portrays the dynamism of zakat by highlighting pertinet issues on the management of zakat institutions and innovative programemes that are design as effectuve distributiton mechanism.